TAKLIK TALAK DALAM PERSPEKTIF GENDER - Muthoin, Muthoin (MUWAZAH, 2012)
Abstract : The understanding of concept taklik talak especially on gender perspective is still limited to certain people; therefor socialization should be continously done. Taklik talak intended to guarantee the wives right and to protect them from discrimative and arbitrary of husbands. But then, the couple have the same role to guard againts taklik talak violation. This statement is reverting to the cople’s right and duty formulation that based on equality principle. On this gender perspective, the cople’s right and duty are equal. Reasons that will make the difference their roles were just about reproduction duty like pregnant, bearing children and suckling (to wives) and protect to wive physically and economically (to husband). Abstrak : Pemahaman konsep taklik talak terutama pada perspektif gender masih terbatas pada orang-orang tertentu; sosialisasi untuk itu harus terus dilakukan secara. Taklik talak dimaksudkan untuk menjamin istri yang tepat dan untuk melindungi mereka dari tindakan diskrimatif dan sewenang-wenang dari suami. Pasangan memiliki peran yang sama untuk menjaga terhadap resiko pelanggaran taklik talak. Pernyataan ini kembali kepada perumusan hak dan kewajiban pasangan suami istri yang berdasarkan prinsip kesetaraan. Pada perspektif gender ini, hak suami istri dan kewajiban yang sama. Alasan yang akan membuat perbedaan peran mereka hanya tentang tugas reproduksi seperti hamil, melahirkan anak dan menyusui (untuk istri) dan melindungi istri dan mencari nafkah (suami).